Cognitive reserve and mental health in cognitive frailty phenotypes: Insights from a study with a Portuguese sample - Gaspar, Pedro Miguel; Campos-Magdaleno, María; Pereiro, Arturo X.; Facal, David; Juncos-Rabadán, Onésimo (Frontiers in Psychology, 2022)
Background: Research on prevalence of cognitive frailty phenotypes in community-dwelling older adults in different countries is important to estimate their prevalence and to determine the influence of cognitive reserve and mental health in order to prevent frailty. The aims of this study were to estimate the prevalence of reversible and potentially reversible cognitive frailty (R-CF, PR-CF) in a Portuguese sample of old adults and explore the associations between these phenotypes and demographic, comorbidity, social support, cognitive reserve and mental health factors. Methods: We assessed frailty (Fried criteria) in 250 community-dwelling older adults (179 women) aged 60 years or over (mean 71.04y) without dementia, neurological or psychiatric disorders. Subjective cognitive decline and Mild cognitive impairment were diagnosed according to standard criteria. Charlson-Index, MOS-SS-q, CRIq and GHQ-12 were used for assessing comorbidity, social support, cognitive reserve and mental health respectively. Results: Prevalence of R-CF was 14%, and that of PR-CF, 15.2%. Cognitive frailty profiles differed significantly in relation to education, comorbidity, mental health, and cognitive reserve, but not in age or gender. Multivariate logistic regression showed that age, gender, comorbidity, social support, mental health, and cognitive reserve together predicted R-CF and PR-CF (90% specificity, 75% sensitivity) with significant OR for mental health and cognitive reserve. Discussion: Cognitive reserve and mental health are important factors predicting R-CF and PR-CF. We recommend assessing these factors for early detection of cognitive frailty and promoting psychological well-being and lifestyles that increase cognitive reserve in adults.